γ-rigid solution of the Bohr Hamiltonian compared to the E(5) critical point symmetry - Bonatsos, Dennis; Lenis, D.; Petrellis, D.; Terziev, P.; Yigitoglu, I. (HNPS Advances in Nuclear Physics, 2019)
A γ-rigid solution of the Bohr Hamiltonian for 7 = 30° is derived, its ground state band being related to the second order Casimir operator of the Euclidean algebra E(4). Parameter-free (up to overall scale factors) predictions for spectra and B(E2) transition rates are in close agreement to the E (5) critical point symmetry, as well as to experimental data in the Xe region around A = 130.